Síntese e caracterização de nanopartículas semicondutoras com estrutura tipo "núcleo/casca" CdxMn1-xS/CdSe obtidas por rota coloidal aquosa - Vanessa Modelski Schatkoski (2011)
Colloidal luminescent semiconductor nanocrystals, also known as quantum dots, have attracted considerable attention due to their significant potential application. The doping of nanocrystalline semiconductors with divalent manganese ions results in new opticalproperties of these semimagnetic semiconductor quantum dots.In this work we report the synthesis and characterization CdxMn1-xS/CdSe quantum dots with core/shell structure to the applications such luminescent biomarkers. The samples were synthesized in aqueous solution at room temperature using poly(vinyl alcohol) as stabilizing agent. Different fractions of Cd2+/Mn2+ ions were investigated aiming the production of stable nanoparticles with different photoluminescence properties. Different shell thicknesses of CdSe were growth on CdxMn1-xS cores. The optical proprieties of the resulting samples were studied by UV-visible spectroscopy and photoluminescence spectroscopy. The morphological characterization was carried out with transmission electrons microscopy (TEM) and Atomic Force Miroscopy (AFM). In addition, Magnetic Force Microscopy (MFM) was used to evaluate the magnetic properties of CdxMn1-xS cores. The results have shown the influence of the Mn2+ partially replacing Cd2+ in the optical behavior of the semiconductor QDs produced. The TEM images have not indicated any detectable segregation or phase separation caused by the Mn2+ added to the CdS system. Through the results of MFM was not possible to observe magnetic interactions in the samples Moreover, the results indicate the formation of CdS/CdSe core/shell nanoparticles and the formation of CdxMn1-xS(Se) alloys. This novel nanostructured system opens a wide window of possibilities in biomedical research and possible applications as biomarkers with magnetic proprieties.